МЕТОДОЛОГІЧНІ ПИТАННЯ УПРАВЛІННЯ СОЦІАЛЬНО-ТРУДОВИМИ ВІДНОСИНАМИ - Vuychenko, Maryna (Zhytomyr Ivan Franko State University, 2022)
The article considers socio-labor relations as a complex of economic, social, political, legal, socio-cultural, psychological and administrative methods and norms aimed at the effective inclusion and adequate reproduction of the workforce in the labor process on a market basis. Management of social and labor relations is a complex of relations between employees and employers, formed on the basis of market demand, supply and price of labor. It is noted that managerial activity is one of the oldest manifestations of social relations and social interaction of people. It is directly related to inequality in all its manifestations, which requires certain organizational actions, the implementation of conscious decisions, certain volitional efforts. And this leads to the emergence of an appropriate field for management-subordination relations, that is, the basic relations of managerial activity. It is substantiated that the decisive role in the management of social and labor relations belongs to the state, which guarantees citizens a free choice of types of labor activity, promotes employment and employment of workers in accordance with their education and qualifications, abilities and vocations, as well as the real needs and requirements of employers for the quality of employees and the state of the market labor "Management-subordination" relationships can be manifested in any form: voluntary or forced, desired or forced, internal or external, development of managerial decisions and their implementation in practical activities. It is emphasized that there are ongoing disputes among specialists regarding the relationship between the categories of "management", "leadership" and "management". Sometimes they are used as synonyms. The article determines that the current state of the theory and practice of management requires the development of new methodological approaches regarding various aspects of management, social mechanisms for making and implementing management decisions, features of management in various types of social organizations, criteria for the effectiveness of management activities, etc. Specialists pay attention to the diversity and variety of existing management approaches: "pulsating management", "innovative management", "transformative management", "self-management", "anti-crisis management", etc.